Family Determinants of Social Maladjustment and Juvenile Delinquency according to Natalia Han-Ilgiewicz - Paulina Perska-Gradowska (Jagiellonian University Press, 2023)
The purpose of the article is to review the key thoughts of Natalia Han-Ilgiewicz on the causes of social maladjustment and criminal delinquency in minors, related to the family environment. The text is based on the analysis of the content of selected works and research by the Polish scholar. According to Han-Ilgiewicz, among the most important causes of social maladjustment related to the functioning of the family are inadequate child-rearing practices and contacts, lack of strong family ties, the improper structure of relations in the family, and imitation of inappropriate behaviours. Translated from Polish by Marta Robson Rodzinne uwarunkowania niedostosowania społecznego i przestępczości nieletnich według Natalii Han-Ilgiewicz Celem artykułu jest zrekonstruowanie najważniejszych myśli Natalii Han-Ilgiewicz dotyczących przyczyn niedostosowania społecznego i wykolejenia przestępczego nieletnich, związanych ze środowiskiem rodzinnym. Tekst został oparty na analizie treści wybranych prac i wyników badań polskiej badaczki. Według Natalii Han-Ilgiewicz wśród najważniejszych przyczyn niedostosowania społecznego związanych z funkcjonowaniem rodziny należy wymienić nieodpowiednie praktyki wychowawcze i kontakty, brak więzi rodzinnej, niewłaściwy układ stosunków w rodzinie oraz naśladownictwo.